Prevalence of Non-Dermatophytic Molds Associated with Cutaneous Mycoses in Cattle in Abia and Imo States, Nigeria - , C. N. Nwofor; , C. A. Oyeka; , N. E. Onyenwe; , M. O. Echeta; , Y. M. Tatfeng (Archives of Current Research International, 2021)
Aims: To study the prevalence and identification of non-dermatophytic molds associated with cattle in Abia and Imo States, Nigeria. Study Design: The systematic random sampling method was adopted. Place and Duration of Study: A total of 2255 cattle was encountered, out of which 451 skin samples from both infected and asymptomatic animals were sampled from six cattle markets in Abia and Imo States, Nigeria between January and August, 2018. Methodology: The 451 samples were analysed for their colonial and microscopic morphology and molecular analysis. Polymerase chain reaction of the 16SrRNA internal transcriber spacer (ITS) sequence techniques were carried out on the isolates. Pathogenicity of the isolates were determined. Results: A total of 16 non-dermatophytic molds were obtained from 451samples analysed at different frequency of occurrences from the cattle skins in both states and these include Aspergillusfumigatus (3.6%), Aspergillus terreus (2.7%), Aspergillus wewitschiae (13.5%), Aspergillus flavus (10.0%), Aspergillus aculeatus (9.0%), Aspergillus sydowii (5.0%), Fusarium solani (3.2%), Fusarium lichenicola (17.9%), Fusarium succisae (12.0%), Fusarium oxysporum (2.0%), Penicillium citrinum (3.0%), Curvularia kusanol (0.6%), Cladosporium tenuissimum (4.9%), Pestalotiopsis microspora (0.1%), Talaromyces kendrickii (0.1%) and Absidia specie (12.9%). Conclusion: The study revealed that non-dermatophytic molds were highly prevalent and are possible causative agent of cutaneous mycoses in cattle. Pathogenicity evaluation carried out in this study revealed that Aspergillus welwitschiae, Cladosporium tenuissimum and Absidia sp. were highly virulent.